HUBUNGAN STUNTING DENGAN PERKEMBANGAN ANAK BATITA DI KECAMATAN PANJANG KOTA BANDAR LAMPUNG - Lupiana, Mindo; Mulyani, Roza; Muliani, Usdeka; Yunianto, Andi Eka (Jurnal Kesehatan Tambusai, 2021)
Stunting is a disorder and problem for children's growth and development if it is handled early so that. This study aims to determine the relationship between stunting and the development of toddlers. The study used a cross-sectional research design. This research was conducted in Panjang District, Bandar Lampung City. The subjects of this study were toddlers aged 1-3 years with stunting with a total sample of 84 children. The chi-square test was used to analyze the relationship between stunting, mother's education, mother's occupation, and toddler development. The results showed that there was a significant relationship between stunting and the development of toddlers p = 0.002, while education (p = 0.371) and mother's occupation (p = 0.229) had no relationship with the development of toddlers. The conclusion is that the status of efforts that can be made to deal with stunting toddlers is to improve the abilities and skills of mothers and cadres in providing stimulation to the development of stunting children optimally and strive for the child's developmental body to take place in harmony both in terms of physical, mental and psychosocial and improve sanitation. environment and hygiene as a preventive effort against infectious disease attacks in stunting toddlers.